KEPEMIMPINAN VISIONER DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM - Asmuni Asmuni (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2016)
Visionary leadership is the ability of a leader in creating, formulating, communicating, socializing, transform and implement ideas that came from her ideal or as a result of social interaction between members of the organization and stakeholders are believed to be the ideals of the organization in the future to be achieved or realized through the commitment of all personnel. This study used a qualitative approach with case studies (case study). Through the analysis of this study, researchers found that (1) the characteristics of visionary leaders in Bani Hasyim Foundation; (2) efforts to realize the vision of the foundation leaders into action is IMTAQ, IPTEK and AKMAL; (3) implications of visionary leaders is their human resources development program teacher, make a pilot school, graduates have the life skills / expertise.